Recombinant plasminogen activator inhibitor-1 reverses the bleeding tendency associated with the combined administration of tissue-type plasminogen activator and aspirin in rabbits. - Vaughan, D E; Declerck, P J; De Mol, M; Collen, D (The Journal of Clinical Investigation, 1989)
The major side effect of thrombolytic therapy is bleeding; however, the pathogenesis of this potential complication is not well understood. Accordingly, we examined the effects of aspirin and recombinant human tissue-type plasminogen activator (rt-PA) on serial template bleeding times and on hemostasis parameters in rabbits. The administration of intravenous aspirin (15 mg/kg) produced a slight prolongation in bleeding times, from 2.1 +/- 0.5 to 2.6 +/- 0.5 min (mean +/- SD, n = 26, P less than 0.01), whereas rt-PA (1 mg/kg per h for 2 h) lengthened the bleeding time from 2.4 +/- 0.3 to 3.2 +/- 0.6 min (n = 5, P = NS). Combination of aspirin with 0.5 mg/kg per h of rt-PA for 2 h prolonged the bleeding time from 2.5 +/- 0.4 to 6.2 +/- 0.9 min (n = 10, P less than 0.01), with an associated fibrinogen decrease of approximately 15%. The combination of aspirin with 1 mg/kg per h of rt-PA for 2 h prolonged the bleeding time from 3.0 +/- 0.3 to 8.3 +/- 1.4 min (n = 8, P less than 0.01) and simultaneously induced a decrease of plasma fibrinogen by approximately 40%. Virtually all animals treated with rt-PA and aspirin manifested a bleeding tendency, as evidenced by spontaneous rebleeding at sites of previously performed template bleeding times or oozing at the femoral venous catheterization site. Intravenous bolus injection of 1 mg/kg of guanidine hydrochloride-reactivated recombinant human plasminogen activator inhibitor-1 (rPAI-1) at the end of the rt-PA infusion resulted in complete reversal, within 5 min, of the prolongation of the bleeding time, and in a disappearance of the bleeding tendency. Nonreactivated rPAI-1 and tranexamic acid were significantly less potent in reversing the bleeding time prolongation. These findings indicate that aspirin and rt-PA given separately do not markedly affect the template bleeding time, but in combination induce a marked prolongation associated with a significant bleeding tendency. This bleeding time prolongation can be rapidly normalized by the administration of reactivated rPAI-1.